2016
DOI: 10.1099/mic.0.000283
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas gene-editing reveals RsmA and RsmC act through FlhDC to repress the SdhE flavinylation factor and control motility and prodigiosin production in Serratia

Abstract: SdhE is required for the flavinylation and activation of succinate dehydrogenase and fumarate reductase (FRD). In addition, SdhE is conserved in proteobacteria (α, β and γ) and eukaryotes. Although the function of this recently characterized family of proteins has been determined, almost nothing is known about how their genes are regulated. Here, the RsmA (CsrA) and RsmC (HexY) post-transcriptional and post-translational regulators have been identified and shown to repress sdhEygfX expression in Serratia sp. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Similarly, in P. carotovorum (Wang et al, 2018) and Serratia sp. ATCC 39006 (Wilf et al, 2013; Hampton et al, 2016), attenuation of flagellar motility was observed in hfq -deletion mutant strains, as an expression of the flhD C genes was dependent on Hfq. Given that sRNAs namely, ArcZ, OmrAB, and RyeB/SdsR, were also identified in our sRNA sequencing data (Supplementary Table S2), and that their wild-type transcript levels are dependent on the functional copy of hfq (Figure 9), we hypothesize that Hfq, in conjunction with the identified sRNAs, may regulate the flagellar motility of P. ananatis in a similar manner as the other enterobacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in P. carotovorum (Wang et al, 2018) and Serratia sp. ATCC 39006 (Wilf et al, 2013; Hampton et al, 2016), attenuation of flagellar motility was observed in hfq -deletion mutant strains, as an expression of the flhD C genes was dependent on Hfq. Given that sRNAs namely, ArcZ, OmrAB, and RyeB/SdsR, were also identified in our sRNA sequencing data (Supplementary Table S2), and that their wild-type transcript levels are dependent on the functional copy of hfq (Figure 9), we hypothesize that Hfq, in conjunction with the identified sRNAs, may regulate the flagellar motility of P. ananatis in a similar manner as the other enterobacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis showed that, in addition to the gas vesicle proteins, RsmA abundance was negatively affected, whilst RbsR and SmaI/SmaR were not detected. RsmA also inhibits flagellar motility and prodigiosin production in S39006 via negative control of the flagella master regulator, FlhDC (Williamson et al, 2008;Wilf et al, 2013;Hampton et al, 2016). In a floR mutant, we observed increased RsmA levels and the high levels of motility related proteins.…”
Section: Discussionmentioning
confidence: 67%
“…RbsR stimulates gas vesicle biogenesis, and prodigiosin, carbapenem, and cellulase production, whilst inhibiting flagellar motility. The mRNA binding protein RsmA promotes expression of both gas vesicle operons, while repressing prodigiosin production and motility (Ramsay et al, 2011;Hampton et al, 2016). In addition, the quorum sensing system (SmaI/SmaR) controls gas vesicle assembly, motility and secondary metabolite elaboration (Thomson et al, 2000;Fineran et al, 2005b;Williamson et al, 2008;Ramsay et al, 2011;Tashiro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a few CRISPR guide RNAs have been designed to target virulence factors, antimicrobials determinants or essential chromosomal genes from specific pathogens, such as E. coli or Staphylococcus aureus (Bikard et al, 2014; Citorik et al, 2014; Gomaa et al, 2014). These systems were employed to efficiently target a particular DNA sequence resulting in the introduction of chromosome deletions in different pathogens, which consequently led to cell death or to the reduction in the population of unwanted bacteria (Vercoe et al, 2013; Bikard et al, 2014; Citorik et al, 2014; Gomaa et al, 2014; Hampton et al, 2016). Vercoe et al (2013) observed that a guide or CRISPR RNA (crRNA) programmed to target a large horizontally acquired island in Pectobacterium atrosepticum activated the endogenous CRISPR-Cas system and promoted the loss of both islands and the accessory genes encoded within.…”
Section: The Crispr-cas Systems In Bacteriamentioning
confidence: 99%